A critical study of the codification of laws with special reference to the Shari'ah - Naeem, Danish (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
When the word 'law' is mentioned there is an invariable belief that this is tantamount to statute or codified law. Any further analyses build upon this assumption; theories are assembled and jurisprudential edifices erected. With the advent of modernity 'law' has overwhelmingly been seen as being interchangeable with 'code' to the point that legal systems without a critical role for codification have been perceived as primitive or elemental with codification deemed to be a symptom of modernity and sophistication. This has confounded the issue of the role of law in society and yielded limited and inadequate possibilities for legal reform. This study analyses the problems involved with the study of a foreign legal system such as Islamic law and the assumptions often inherent in reform. It examines the phenomenon of codification from three different perspectives aiming to clarify the role of codification within an Islamic system. It scrutinizes the functions of codification and questions the assumptions that pervade the discourse advocating codification. It considers the institutions that have a bearing on Islamic law and the extent to which the powers of the executive are circumscribed during its operation. Finally it considers an instance of codified Islamic legal rules in the context of Pakistan and assesses how different courts treat such a rule. The findings of this study reveal that codification is a foreign phenomenon as far as its function and ideology is concerned. It meshes with the human tendency towards self-control and aggrandizes the power of the executive and ultimately the nation-state. Islamic law, if it is to preserve a significant role in the lives of Muslims must require the dominance of the jurist class in the legal domain and remain for the most part uncodified.